Listen: Aplikasi Pendukung Perkembangan Bahasa Anak Berbasis Audiobook : Listen: Application to Support Children's Language Development Based on Audiobooks - Fatimah Khairunnisa; M. Amirullah (Litera Academica Publishing, 2025)
Language development is one of the most crucial aspects of a child’s growth, as it influences cognitive abilities, communication skills, emotional expression, and information acquisition. However, data from the 2021 Susenas MSBP survey indicate that the majority of early childhood children in Indonesia do not receive optimal support from their parents in reading or listening to stories. This article examines the importance of language stimulation in children and introduces Listen, an audio-based digital library application designed to enhance children’s vocabulary exposure and language skills in an adaptive and educational manner. The application leverages technology to provide audiobooks and interactive features that serve as an innovative literacy medium. The findings highlight that environmental support, both from parents and digital learning media, plays a significant role in strengthening children’s language development. Therefore, Listen offers a flexible and effective alternative solution to support children’s language growth as part of preparing them to become competent future generations.